2023
DOI: 10.1111/tid.14024
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcomes of COVID‐19 in vaccinated hematopoietic stem cell transplant recipients: A single‐center experience

Abstract: Introduction A high incidence of mortality and severe COVID‐19 infection was reported in hematopoietic stem cell transplant (HSCT) recipients during the early phases of the COVID‐19 pandemic; however, outcomes with subsequent severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants, such as the omicron variant, have yet to be reported. Additionally, rollout of COVID‐19 vaccinations in subsequent pandemic waves may modify COVID‐19 disease severity and mortality in this immunocompromised population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…COVID‐19 clinical characteristics, medication used, and lethality are reported in Table 3. From the studies that reported symptomatic rate 7,11,15,21–26 we found 79.4% of symptomatic disease ( n = 624/785, range: 50.0% 26 to 100% 15,23 ). The hospitalization rate varied from 9.2% 26 to 74.0% 10 and the median duration of hospital stay from 14 7 to 8 11 days.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…COVID‐19 clinical characteristics, medication used, and lethality are reported in Table 3. From the studies that reported symptomatic rate 7,11,15,21–26 we found 79.4% of symptomatic disease ( n = 624/785, range: 50.0% 26 to 100% 15,23 ). The hospitalization rate varied from 9.2% 26 to 74.0% 10 and the median duration of hospital stay from 14 7 to 8 11 days.…”
Section: Resultsmentioning
confidence: 87%
“…The most frequent hematological underline disease was acute myeloid leukemia in eight (50.0%) articles 7,10,15,19,22,23,25,26 . Allogeneic HSCT patients were the majority in most studies, 7,10,15,18,19,21–26 with a total of 861 patients (72.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haematologists suggest that these patients should maintain multi‐modal prevention, such as infection‐prevention behaviours, vaccination and an antiviral antibody drug 1 . A study reported positive outcomes in a cohort of highly vaccinated HSCT recipients with COVID‐19 caused by the omicron variant as well as previous strains 15 …”
Section: Introductionmentioning
confidence: 99%
“…1 A study reported positive outcomes in a cohort of highly vaccinated HSCT recipients with COVID-19 caused by the omicron variant as well as previous strains. 15 Immunogenicity after SARS-CoV-2 vaccination, especially humoral immunity, is generally assessed by enzyme-linked immunosorbent assay (ELISA) using an anti-SARS-CoV-2 spike IgG antibody. 16 To date, the reactivity of vaccination has been evaluated by the measurement of antibody titers after vaccination in both healthy individuals and also in patients with various immune states, such as cancer patients.…”
mentioning
confidence: 99%